Solid‐State Photochemical [2+2] Cycloaddition Reaction of MnII Complexes. Issue 44 (8th July 2019) - Yadava, Khushboo; Vittal, Jagadese J.
Abstract: Three Mn II complexes have been synthesized under similar experimental conditions. Of these [Mn2 (benzoate)4 (L)2 ] (where L=4‐styrylpyridine or 4spy, 1 and 2‐fluoro‐4′‐styrylpyridine or 2F‐4spy, 3 ) are paddlewheel complexes, but crystallized in different space groups. Whereas [Mn2 (benzoate)4 (3F‐4spy)4 ] (3F‐4spy=3‐fluoro‐4′‐styrylpyridine), 4 is a dinuclear complex having different stoichiometry from 1 and 3 with two pairs of 3F‐4spy ligands aligned in face‐to‐face manner. An irreversible phase transition occurs from the space group P 21 / c to C 2/ c when 1 was heated up to 125 °C to 2 in a single‐crystal‐to‐single‐crystal fashion or when ground 1 to powder. 2 is isomorphous and isostructural to 3 . Complimentary π–π interactions in head‐to‐tail alignment of the styrylpyridine ligands furnishes 1D aggregates in 1 –3 which are congenial to undergo [2+2] cycloaddition reaction under UV light. Whereas, face‐to‐face alignment of the 4spy pairs in 4 is expected to provide a head‐to‐head photoproduct. All the Mn II complexes are indeed found to be photoreactive. To our surprise, contrary to their Zn II analogues, 2 and 3 were not found to be photosalient. The percentage volume expansion during the photoreaction as determined from the density measurements, was found to be too low (3.2 and 4.6 % respectively for 2 and 3 ) to have this behavior. Abstract : What a surprise ! Three Mn II complexes of 4‐styrylpyridine derivatives undergo [2+2] cycloaddition reactions in the solid state but gave different photoproducts due to different alignments of the ligands. The paddlewheel complexes were surprisingly not photosalient although they are isomorphic to Zn II complexes.